1997
DOI: 10.1262/jrd.43.121
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Administration of Fatty Acids-Enriched Mold Dried Cell Containing .GAMMA.-Linolenic Acid to Female Pigs Improves Ovulation Rate and Embryo Quality in Summer.

Abstract: Abstract. The effect of dietary administration with essential unsaturated fatty acids, linoleic acid [18:2 (n-6)], a mixture of oleic acid [18:1 (n-9)], linoleic acid and γ-linolenic acid [18:3 (n-6)], or α-linolenic acid [18:3 (n-3)], on early embryo development of pubertal female pigs in summer was examined. Safflower oil was supplemented to a concentrated diet (the control diet) at the rate of 5% (Safflower oil-diet). The concentration of linoleic acid was 3.75 g/100 g in the Safflower oil-diet. Fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
4
0
2
Order By: Relevance
“…Several articles have been published on the effect of nutrition on superovulation in pigs (Kojima et al, 1997) and cows (Boland et al, 2001;Fouladi-Nashta et al, 2007;Cerri et al, 2009). However, only a few studies, which have reported contradictory results, were focused on the evaluation of oocyte quality in relation to diet composition.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles have been published on the effect of nutrition on superovulation in pigs (Kojima et al, 1997) and cows (Boland et al, 2001;Fouladi-Nashta et al, 2007;Cerri et al, 2009). However, only a few studies, which have reported contradictory results, were focused on the evaluation of oocyte quality in relation to diet composition.…”
Section: Discussionmentioning
confidence: 99%
“…Há relatos de efeito dos ácidos graxos sobre: o número e o tamanho de folículos ovarianos (Lucy et al, 1991;Robinson et al, 2002;Bilby et al, 2006); o tamanho do corpo lúteo (CL) (Raes et al, 2004;Bilby et al, 2006); e a qualidade ovocitária (Kim et al, 2001;Zeron et al, 2002). Além disso, outros autores também observaram que dietas que continham ácidos graxos influenciaram a qualidade embrionária (Kojima et al, 1997;Childs et al, 2008a;Cerri et al, 2009) e a concentração circulante de prostaglandina e hormônios esteroides (Ryan et al, 1992;Petit et al, 2002;Childs et al, 2008b). Neste último caso, não estão bem definidas as causas da associação observada entre a suplementação com lipídeos e as maiores concentrações circulantes de hormônios esteroides.…”
Section: Introductionunclassified
“…They play a key role in growth and development of all body organs and determine some of their properties. Essential PUFAs are also precursors of eicosanoids, prostaglandins and leucotriens (Kojima et al, 1997). Recently, also CLA is in focus of interest, viz.…”
mentioning
confidence: 99%